Effect Of Work Satisfaction, Financial Compensation And Work Competency Of Employee Performance In PT Inter Wahana Nusantara Medan: Effect Of Work Satisfaction, Financial Compensation And Work Competency Of Employee Performance In PT Inter Wahana Nusantara Medan - Reinaldo Kosasih; Welliam Welliam; Roynaldo Roynaldo; Holfian Daulat Tambun (Institute of Computer Science (IOCS), 2020)
This research was conducted at PT Inter Wahana Nusanatara Medan. The research objective is to obtain job satisfaction, financial compensation and competence on employee performance at PT Inter Wahana Nusanatara Medan. The population and sample in this study were 82 employees. The research method uses multiple linear regression analysis. The results of this study indicate the simultaneous work results of job satisfaction, financial compensation and work competence on employee performance at PT Inter Wahana Nusanatara Medan. Partially job satisfaction, financial compensation and work competence on employee performance at PT Inter Wahana Nusanatara Medan.